ASRAMA MAHASISWA UNIVERSITAS MUSAMUS MERAUKE (PENERAPAN DESAIN GREEN ARCHITECTURE) - Yosi Valentina Simorangkir; Anton Topan; Muchlis Alahudin; Ragil Hidayat (Musamus Journal of Architecture, 2018)
Musamus University student dormitory is one of the facilities provided by the University for students, especially those from outside the area or distant homes. The design of this student dormitory can provide good facilities for the convenience of its occupants by applying the philosophy of honeycomb design and themes as well as the application of Green Architecture designs. Research uses descriptive method, namely to look for elements, characteristics, traits. Descriptive methods are carried out through: surveys, documentation and interviews. Where the data obtained will be a reference to the dormitory design. The number of UNMUS students until 2016 is 9,000 students, 60% of the total number of students in the dormitory is 4,000 students (boys and girls). The area of ​​the student dormitory is 90,000 m2 (9 Ha). Dormitory residents with a percentage of 59% of sons and 41% of daughters, division of dormitory class which consists of class 1: sons (1416), daughters (984), class 2putra (708) and daughters (492) and class 3: sons (236) and daughters (164). The application of Green Architechture is expected to maximize natural resources, including: utilization of rainwater, maximizing natural lighting (skylights), enlarging openings (openings can be penetrated by light and air), with the building stage, air can flow in the building properly, arrangement / building design patterns and vegetation planting are expected to inhibit wind speed. Kata Kunci:Asrama Mahasiswa.,Green Architecture., Universitas Musamus Merauke.